Male-sterile rice seed production - Bragantini, Claudio; Guimarães, Elcio Perpétuo; Cutrim, Veridiano dos Anjos (Pesquisa Agropecuaria Brasileira, 2001)
Commercial male-sterile rice (Oryza sativa L.) seed production is one of the limitations to allow large scale hybrid seed production. This work studied three ratios between male-sterile line (A line) and maintainer (B line). The A:B ratios used in the study were: 8:4, 10:2 and 14:4. The evaluated traits to determine which ratio is more suitable were: number and percentage of filled grains per panicle and number of pollen grains per unit area. The 8:4 ratio produced statistically significant higher percentage of filled grains per panicle than the other two, but proportionally it requires more field area for the B line. Statistical differences were observed for percentage of filled grains per panicle among samples collected in the different rows at different distances from the pollen source. These results were strongly influenced by the predominant wind direction. The number of pollen grains was statistically the same for all ratios and distances, therefore it did not play a major role in percentage of filled grain per panicle. The results allow to conclude that 10:2 ratio has the highest potential for male-sterile line seeds production.